2017
DOI: 10.1177/1103308817705258
|View full text |Cite
|
Sign up to set email alerts
|

An Endeavour for Autonomy

Abstract: In discussion of troubled adolescent girls, their mental health often is in focus and a discourse constructing girls as vulnerable victims therefore dominates Swedish social services and secure care. This article is an investigation of how the girls themselves are navigating the discursive terrain where understandings of troubled adolescent girls in secure care are regulated. The results show that even though the girls’ stories show considerable similarities with what is previously known about troubled adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…There can be restrictions on clothing and the use of make‐up and other forms of expression of self and identity. These behavioural regulations constitute forms of soft power, which shape how adolescents in institutional care can perform their gendered, sexual or ethnic selves (Andersson Vogel, 2018; Henriksen, 2018; Sankofa et al, 2018). The regulatory practices aimed at providing adolescents with social skills and behaviour in accordance with social norms, thus serving purposes of rehabilitation and care, while they can be experienced as micromanagement, punishment and devaluations of who they desire to be.…”
Section: Findings: Exploring Coercion In the Everyday Institutional L...mentioning
confidence: 99%
“…There can be restrictions on clothing and the use of make‐up and other forms of expression of self and identity. These behavioural regulations constitute forms of soft power, which shape how adolescents in institutional care can perform their gendered, sexual or ethnic selves (Andersson Vogel, 2018; Henriksen, 2018; Sankofa et al, 2018). The regulatory practices aimed at providing adolescents with social skills and behaviour in accordance with social norms, thus serving purposes of rehabilitation and care, while they can be experienced as micromanagement, punishment and devaluations of who they desire to be.…”
Section: Findings: Exploring Coercion In the Everyday Institutional L...mentioning
confidence: 99%
“…Although this is true for more serious and violent crimes, self‐report studies have shown that adolescent males and females commit minor, non‐violent offenses (e.g., status offenses, stealing/shoplifting) at equal rates (Loeber et al, 2017b). Research into antisocial behaviors of adolescent females has often focused on the small group of young women with extensive problems, such as young females in gangs, or within secure care (Andersson Vogel, 2018; Gushue & McCuish, 2021; O'Neal et al, 2016). Less focus and attention have been paid to the comparatively larger group of adolescent females who commit crimes, but whose delinquency is limited and, therefore, leads to non‐custodial sanctions.…”
Section: Introductionmentioning
confidence: 99%